ENHANCING STUDENTS’ CREATIVE AND PROFESSIONAL DEVELOPMENT IN VISUAL ARTS LESSONS: PEDAGOGICAL AND PSYCHOLOGICAL APPROACHES - Eshmatov Samariddin Hamza oʻgʻli (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores pedagogical and psychological methods to enhance students’ creative and professional development in visual arts lessons. It examines the role of interactive teaching methods, project-based learning, individualized support, and motivational strategies in fostering students’ artistic skills and professional competencies. The study emphasizes the importance of a supportive classroom environment and tailored teaching approaches to maximize students’ creative potential and professional growth.